Health-related quality of life and unmet healthcare needs in Huntington's disease. Issue 1 (January 2017) - van Walsem, Marleen; Howe, Emilie; Ruud, Gunvor; Frich, Jan; Andelic, Nada
Abstract Background Huntington's disease (HD) is a rare neurodegenerative disorder with a prevalence of 6 per 100.000. Despite increasing research activity on HD, evidence on healthcare utilization, patients' needs for healthcare services and Health-Related Quality of Life (HRQoL) is still sparse. The present study describes HRQoL in a Norwegian cohort of HD patients, and assesses associations between unmet healthcare and social support service needs and HRQoL. Methods In this cross-sectional population-based study, 84 patients with a clinical diagnosis of HD living in the South-East of Norway completed the HRQoL questionnaire EuroQol, EQ-5D-3L. Unmet needs for healthcare and social support services were assessed by the Needs and Provision Complexity Scale (NPCS). Furthermore, functional ability was determined using the Unified Huntington's Disease Rating Scale (UHDRS) Functional assessment scales. Socio-demographics (age, gender, marital status, occupation, residence, housing situation) and clinical characteristics (disease duration, total functional capacity, comorbidity) were also recorded. Descriptive statistics were used to describe the patients' HRQoL. Regression analyses were conducted in order to investigate the relationship between unmet healthcare needs and self-reported HRQoL. Results The patients were divided across five disease stages as follows: Stage I:n = 12 (14%), Stage II:n = 22 (27%), Stage III:n = 19 (23%), Stage IV:n = 14 (16%), and Stage V:n = 17 (20%). Overall HRQoL was lowest in patients with advanced disease (Stages IV and V), while patients in the middle phase (Stage III) showed the most varied health profile for the five EQ-5D-3L dimensions. The regression model including level of unmet needs, clinical characteristics and demographics (age and education) accounted for 42% of variance in HRQoL. A higher level of unmet needs was associated with lower HRQoL (β value - 0.228;p = 0.018) whereas a better total functional capacity corresponded to higher HRQoL (β value 0.564;p < 0.001). Conclusions The study findings suggest that patients with HD do not receive healthcare services that could have a positive impact on their HRQoL.